If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -2(1 + -1m) = 0 9m + (1 * -2 + -1m * -2) = 0 9m + (-2 + 2m) = 0 Reorder the terms: -2 + 9m + 2m = 0 Combine like terms: 9m + 2m = 11m -2 + 11m = 0 Solving -2 + 11m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 11m = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 11m = 0 + 2 11m = 0 + 2 Combine like terms: 0 + 2 = 2 11m = 2 Divide each side by '11'. m = 0.1818181818 Simplifying m = 0.1818181818
| y^2-3y=7 | | 0.12(6)0.02x=0.04(6+x) | | 8*12+6y=48 | | 6x-29-28=9 | | 2n^2+37n-19=0 | | v^2-8v+7=0 | | (6b^3+3b^2+8)-(2b^3-8b^2+6b-5)= | | 6x-29+28=9 | | 2x^2-39x+19=0 | | 8*0+6y=48 | | x+13-26+5=179 | | 3x^3+x-2=0 | | 3x-12=4+x | | -.003x^2+.23x+60=0 | | 5(4x-1)-3(3x-3)=5(2x+5)-10 | | -x^2+8x+10=0 | | u-3.75=9.5 | | 5(2x-2)=10x(x+1) | | 2(x-7)=5(x+3)-x | | (x-7)(3x+7)=0 | | -0.75x=24 | | -2(5s-3)-6=-3(8s+6)-5 | | 5-(6-6x)=2x-4 | | 3+3x-1=9x+10-2x | | 2(X-12)=0 | | -1.25+0.15x=0 | | P(x)=x^3+3x^2-x-3 | | 6r*5r^2= | | x^3-12x^2+11x=0 | | (4)-2x(4)5= | | -7(3p+3)-15=3(2p+6) | | (3t)2-3= |